The 2019 Philippine UHC Act, Pandemic Management and Implementation Implications in a Post-COVID-19 World: A Content Analysis - Bautista, Maria Cristina G (Archīum Ateneo, 2022)
The 2019 Philippine Universal Health Care Act (Republic Act 11223) was set for implementation in January 2020 when disruptions brought on by the pandemic occurred. Will the provisions of the new UHC Act for an improved health system enable agile responses to forthcoming shocks, such as this COVID-19 pandemic? A content analysis of the 2019 Philippine UHC Act can identify neglected and leverage areas for systems’ improvement in a post-pandemic world. While content or document analysis is commonly undertaken as part of scoping or systematic reviews of a qualitative nature, quantitative analyses using a two-way mixed effects, consistency, multiple raters type of intraclass correlation coefficient (ICC) were applied to check for reliability and consistency of agreement among the study participants in the manual tagging of UHC components in the legislation. The intraclass correlation reflected the individuals’ consistency of agreement with significant reliability (0.939, p < 0.001). The assessment highlighted a centralized approach to implementation, which can set aside the crucial collaborations and partnerships demonstrated and developed during the pandemic. The financing for local governments was strengthened with a new ruling that could alter UHC integration tendencies. A smarter allocation of tax-based financing sources, along with strengthened information and communications systems, can confront issues of trust and accountability, amidst the varying capacities of agents and systems.